2021
DOI: 10.4084/mjhid.2021.017
|View full text |Cite
|
Sign up to set email alerts
|

Real world data on characteristics and management of community patients receiving anticoagulation therapy who presented with acute bleeding to the emergency department at a regional Australian hospital: A prospective observational study.

Abstract: Objective: To study patients receiving anticoagulants with or without antiplatelet therapy presenting at a regional Australian hospital with bleeding.  The main aims are to explore: (1) patients’ characteristics and management provided; (2) association between the type of anticoagulant and antiplatelet agent used and the requirement of reversal;  (3) and the length of hospital stay (LoS) in conjunction with bleeding episode and management. Methods: A prospective cross-sectional review of medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[ 14 ] showed that the CYP2C9 and VKORC1 genotypes were able to identify patients with venous thromboembolism (VTE) who were at increased risk of bleeding due to warfarin anticoagulation. Many warfarin-treated patients develop acute bleeding and the INR in many patients on warfarin exceeded the target for their condition [ 15 ]. Gage BF et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] showed that the CYP2C9 and VKORC1 genotypes were able to identify patients with venous thromboembolism (VTE) who were at increased risk of bleeding due to warfarin anticoagulation. Many warfarin-treated patients develop acute bleeding and the INR in many patients on warfarin exceeded the target for their condition [ 15 ]. Gage BF et al .…”
Section: Discussionmentioning
confidence: 99%